PROSPECTS FOR DEVELOPMENT OF THE GAS PROCESSING INDUSTRY IN UZBEKISTAN - Shamshod Gafurov (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This article analyzes the current level of development, existing problems and promising directions of the gas processing industry in the Republic of Uzbekistan. Method: The study considers the possibilities of diversifying the industry, creating import-substituting products and increasing export potential through the production of polymers, liquefied gas, synthetic fuels and chemicals. Result: The fact that the export of natural gas is economically inefficient, the need to produce products with high added value through its local processing is justified. The issues of technological modernization, attracting foreign investment and optimizing existing production capacities are also analyzed. Novelty: The author puts forward practical proposals on advanced practices in the field of deep gas processing, mechanisms for making the industry competitive, and improving the investment climate.